PELAKSANAAN PENDIDIKAN KARAKTER DALAM PEMBELAJARAN AKHLAK MAHASISWA PGMI - Hasanah, Nur (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2009)
The study are aimed to determine the students’ character education of Islamic Primary Teacher Education (PGMI) department, the implementation also the factors inhibiting and supporting the implementation of character education in the learning morals (akhlak) of PGMI students. This study focuses on the implementation of students’ character education in Islamic Primary Teacher Education (PGMI) department. The subjects of this research are the lecturers of moral (akhlak) subject and the fourths semester students of Islamic Primary Teacher Education (PGMI) department STAIN Salatiga. The data is collected by observation, interviews, and documentation. Research findings show that character education of Islamic Primary Teacher Education (PGMI) department students have been in a good condition. The only curiosity and care to environment indicators that still less. The implementation strategy in this research is by example, parable, habituation and advice or warning. While the inhibiting and supporting factors are derived from the internal factors of individual students and families as well as the contributing factors. While the external factors are instructional methods and media as well as campus and community environmental factors. Campus and community environmental factors become the obstacle to implement the character education of Islamic Primary Teacher Education (PGMI) department students.